Transforming Strategies in The Digital Era: The Role of social media In Customer Value Analysis and Crisis Management for Tourism Firms - Rehman, Hafiz Mudassir; Amin, Aamir; Rehman, Mobashar; Nematova, Gulshan; Shamim, Amjad; Hossain, Md Billal (Universiti Utara Malaysia Press, 2023)
Social media is gaining popularity nowadays and is increasingly being used by many small and large organisations. Organisations are adopting new social platforms and technologies to achieve their key and effective management strategies. However, there are still opportunities to explore the role of new technologies in developing useful strategies. In current research, the utilisation of technological tools especially social media was examined to improve the customer value analysis in the organisations. Besides, the research of social media use for crisis management is also increasing and the relevant strategies are still being-investigated. To overcome this gap, this research aims to evaluate the impact of the use of social media on customer value analysis and crisis management. To attain this, a detailed questionnaire was adapted from several different studies. Data were collected from a diverse targeted sample of tourism-related firms from all over Malaysia, including hotels, resorts, travel agencies and transportation companies. The model was tested using Smart PLS software and the results were generalised. Overall, this research will add a noteworthy contribution to the literature by highlighting the significance of social media and recognising its urgency during crisis for businesses. It will also help in answering questions regarding the role of social media usage towards customer value analysis and crisis management of organisations in the Malaysian tourism sector. Moreover, the practitioners will use the findings to make strategies for crisis management and build customer value chain.